2060: An Autonomously Crafted Built Environment. (July 2017) - Simondetti, Alvise; Luebkeman, Chris; Uerz, Gereon
Abstract : By 2060, smart technology will allow every aspect of our surroundings to be optimised for efficiency and customisable to our desires. From street lighting, to building maintenance, to hotel interiors, to flood protection – this is the future as imagined by Alvise Simondetti, Chris Luebkeman and Gereon Uerz of Arup's Foresight + Research + Innovation team . After setting out their vision of what lies ahead, they highlight several recent projects that they have worked on with high‐profile architects around the globe: projects that pave the way to a world where fine crafting and intelligent design are for the masses rather than the few. This is all set in context by a piece that outlines the evolutionary steps that have been triggered by disruptive technological shifts.